2019
DOI: 10.21203/rs.2.1751/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detecting influenza and emerging avian influenza virus by influenza and pneumonia surveillance systems in a large city in China, 2005 to 2016

Abstract: Background: Detecting avian influenza virus has become an important public health strategy for controlling the emerging infectious disease. This study aimed to analyze the efficiency of two surveillance systems in detecting the emerging avian influenza viruses. Methods: A modified influenza surveillance system (ISS) and a new built pneumonia surveillance system (PSS) have been used to monitor the viruses in Changsha City, China. The ISS is based on monitoring outpatients in two sentinel hospitals to detect mil… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…A study (12) has confirmed that pneumonia is a lung inflammatory response caused by environmental or viral factors. Early clinical symptoms of pediatric pneumonia, such as mild cough, are not obvious, and are often ignored by parents, and can result in severe pneumonia (13)(14)(15).…”
Section: Discussionmentioning
confidence: 95%
“…A study (12) has confirmed that pneumonia is a lung inflammatory response caused by environmental or viral factors. Early clinical symptoms of pediatric pneumonia, such as mild cough, are not obvious, and are often ignored by parents, and can result in severe pneumonia (13)(14)(15).…”
Section: Discussionmentioning
confidence: 95%